1990
DOI: 10.1108/03090599010001562
|View full text |Cite
|
Sign up to set email alerts
|

Improving Working Relationships: Group Effectiveness Training

Abstract: Working relationships are explored in a workshop situation, between a Personnel Director and Senior Managers, with the object of modifying structures and procedures as well as changes in behaviour. Reference to the literature available was resorted to during the workshop, as well as the differing methods of applying group effectiveness training and exploring the possible solutions to the inherent problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This deficiency is also apparent in much of the published material to date on experiential or team training. Appelbaum [28], Bailey [29], Berger [30,31], Barner [32], Brauchle and Wright [33], Fulmer [12], Holden [34], Huszczo [35], Lusher [36], all cite cases of a particular training programme or suggest "to do" lists to ensure success or minimize failure but none suggest any objective measures of effectiveness. Some others, including Akande [37], Bradford [38], Kazemek [39], Kirkpatrick and Smith [40], go part of the way to suggesting methods to measure effectiveness.…”
Section: Critiques Of Outdoor Trainingmentioning
confidence: 99%
“…This deficiency is also apparent in much of the published material to date on experiential or team training. Appelbaum [28], Bailey [29], Berger [30,31], Barner [32], Brauchle and Wright [33], Fulmer [12], Holden [34], Huszczo [35], Lusher [36], all cite cases of a particular training programme or suggest "to do" lists to ensure success or minimize failure but none suggest any objective measures of effectiveness. Some others, including Akande [37], Bradford [38], Kazemek [39], Kirkpatrick and Smith [40], go part of the way to suggesting methods to measure effectiveness.…”
Section: Critiques Of Outdoor Trainingmentioning
confidence: 99%
“…Originality/value -Very few studies have quantitatively confirmed its effectiveness, which is difficult, given the subjective nature of evaluation (Padilla-Mel e ndez et al, 2014). Authors such as Barner (1989), Huszczo (1990), Lusher (1990), Bailey (1990), Fulmer (1992, Irvine and Wilson (1994) and Wagner and Campbell (1994) mention studies which implemented an outdoor training programme, but few studies attempt an objective evaluation. This study uses these tools in the Asian environment, after their application and confirmation of their measurability in Europe.…”
mentioning
confidence: 99%